(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper’s main goal is to describe the new fractional operators for monotone differentiable function equipped with generalized Mittag-Leffler functions as its kernel, and develop the fractional inequalities for a new family of continuous differentiable convex functions by implementation of newly described fractional operators. Due to the generalized fractional operators to obtain the new version of the Hermite Hadamard type inequalities, and their refinements for continuous differentiable monotone convexities, all the results have significant behavior in the field of analysis, and open new horizon for the modification of inequalities through a new class of convexities. We also spoke about a few unique situations involving the acquired outcome in the framework of the corollaries.